The -675 4G/5G polymorphism at the Plasminogen Activator Inhibitor 1 (PAI-1) gene modulates plasma Plasminogen Activator Inhibitor 1 concentrations in response to dietary fat consumption - Perez-Martinez, P; Adarraga-Cansino, M.D; Fernandez de la Puebla, R.A; Blanco-Molina, A; Delgado-Lista, J; Marín, C; Ordovás, J.M; López-Miranda, J; Pérez-Jiménez, F (British journal of nutrition, 2008)
The objective of the study was to determine whether Plasminogen Activator Inhibitor Type 1 (PAI-1) -675 4G/5G polymorphism is associated with the response of functional plasma PAI-1 concentrations to changes in the amount and quality of dietary fat in healthy subjects. PAI-1 is the major inhibitor of fibrinolysis, and a lower level of fibrinolytic activity could be implicated in an increased risk of IHD. Fifty-nine healthy Spanish volunteers (ten 4G/4G homozygotes, twenty-eight heterozygotes 4G/5G and twenty-one 5G/5G homozygotes) consumed three diets for periods of 4 weeks each: a SFA-rich diet (38 % fat, 20 % SFA), followed by a carbohydrate-rich diet (30 % fat, 55 % carbohydrate) and a MUFA-rich diet (38 % fat, 22 % MUFA) according to a randomized crossover design. At the end of each dietary period plasma lipid and functional plasma PAI-1 concentrations were determined. Subjects carrying the 4G allele (4G/4G and 4G/5G) showed a significant decrease in PAI-1 concentrations after the MUFA diet, compared with the SFA-rich and carbohydrate-rich diets (genotype ×  diet interaction: P = 0·028). 5G/5G homozygotes had the lowest plasma PAI-1 concentrations compared with 4G/4G and 4G/5G subjects (genotype: P = 0·002), without any changes as a result of the amount and the quality of the dietary fat. In summary, no differences in plasma PAI-1 concentration response were found after changes in dietary fat intake in 5G/5G homozygotes, although these subjects displayed the lowest concentrations of PAI-1. On the other hand, carriers of the 4G allele are more likely to hyper-respond to the presence of MUFA in the diet because of a greater decrease in PAI-1 concentrations.